Actio Pauliana: A Legal Remedy for Individual Creditors or for All the Creditors? From Roman Law to the Present Day (Ius Novum, 2026)
The article analyses whether, if a debtor divests themselves of their assets and thereby renders satisfaction of creditors impossible, the right to challenge the debtor’s acts should be vested exclusively in all creditors jointly, appropriately represented, or whether individual creditors should retain the possibility of relying on individual legal remedies. To answer this question, the authors use the dogmatic method, the historical method, and the comparative method. The first section of this paper discusses how creditors were protected under Roman law. After an analysis of the legal remedies available in classical law, the standing to bring an actio Pauliana in Justinian’s law is discussed. Such an actio was available to the curator bonorum acting on behalf of all creditors, but it could also be brought by individual creditors. In contemporary law, the issue discussed in this article arises when a debtor is declared bankrupt. In such a situation, German law does not allow individual creditors to bring or continue individual actions. Until recently, the position under Polish law was similar, but following a recent resolution adopted by the Supreme Court, the prohibition has been relaxed and creditors are allowed to make auxiliary use of individual legal remedies. This is possible primarily when the receiver is unwilling or unable to bring an action on behalf of the bankruptcy estate. The latter approach merits approval, as it properly balances the interests of the parties concerned.